SOSIALISASI PROSEDUR PEMUSNAHAN REKAM MEDIS DI PUSKESMAS WILAYAH KERJA DINAS KESEHATAN KULON PROGO - Harinto Nur Seha (Permata Indonesia, 2023)
Medical record is a document that is used as a media record in serving patients at the health center. Theimplementation of recording using paper media turned out to have several weaknesses including the needfor storage space. Storage space in each public health center has limitations due to the area of the room,the number of rooms, and the availability of storage shelves. The number of medical records will continueto increase at any time, so it is necessary to carry out activities to destroy medical records according toapplicable policies. The results of a preliminary study with the Head of the DPC PORMIKI Kulon Progo andthe Head of 6 public health center Installation, the obstacles faced by the public health center in the KulonProgo Health Office work area are 1) There is no special room for storing inactive medical records due tolimited space, 2) It cannot be destroyed because there are several extermination procedures that involveexternal parties, namely archivists, 3) Lack of medical record and health information graduates in eachhealth center, so they do not understand the procedure and management of medical record disposal. Thisactivity was attended by 120 participants which was held online and offline while adhering to healthprotocols during the Covid-19 Pandemic. The method of implementing this activity is by conductingoutreach to HIM at the Kulon Progo Health Center. This activity includes the presentation of material byresource persons as PMIK experts and resource persons from the Archives and discussions withparticipants. The resulting outputs are 1) procedures and procedures for the destruction of medical records2) optimization and ease of knowledge of PMIK officers in the destruction process which can involve theauthorities.